(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
This article examines the analysis of the relationship between accounting policies and assessing the liquidity of the balance sheet of the organization. This analysis is supported by an illustrative example of the influence of certain provisions of the accounting policy on the accounting of the facts of economic life in a commercial organization and their further reflection in the accounting (financial) statements.